Investigating the efficacy of a varnish containing gallic acid on remineralization of enamel lesions: an in vitro study - Iman Parisay; Marzie Boskabady; Hossein Bagheri; Saber Babazadeh; Melika Hoseinzadeh; Fatemeh Esmaeilzadeh (BMC, 2024)
Abstract This study evaluated the efficacy of a formulated remineralizing gallic acid (GA) varnish in treating artificial enamel caries lesions. Fifty-five intact bovine incisors were collected. Enamel blocks (5 × 9 mm) were prepared. A third of each block's surface remained intact. Primary carious lesions were induced on the middle and bottom thirds of the blocks by immersing the samples in a demineralization solution for 6 h. The bottom third of the blocks were further remineralized by randomly applying 0.5%, 2%, or 8% GA varnishes and 2.26% fluoride varnish (V varnish, Vericom, Seoul, Korea), or the varnish base without active ingredients (n = 11 each). The specimens were immersed in a remineralizing solution for 4 h and then subjected to a 2-hour immersion in the demineralizing solution. After six days of pH cycling, the surface microhardness was measured at depths of 30, 75, and 120 μm. The percentage of surface microhardness recovery (SMHR%) was compared among the groups using the Shapiro-Wilk, ANOVA, and Tukey HSD post-hoc tests (α = 0.05). The SMHR% of all experimental groups was higher than the control group at 30 μm (p < 0.05). The 0.5% GA varnish showed the highest SMHR% at all depths; however, the difference with the other experimental groups was significant at a depth of 30 μm (p < 0.05). The SMHR% of the fluoride and the 2% and 8% GA varnishes was comparable at all depths. All treatments potentially remineralize enamel lesions, with 0.5% GA varnish having the greatest effect, particularly on the top surface layer. As such, this newly developed varnish may emerge as a promising alternative to fluoride varnish.